2021
DOI: 10.1002/anie.202016129
|View full text |Cite
|
Sign up to set email alerts
|

Boosting CO2 Electrochemical Reduction with Atomically Precise Surface Modification on Gold Nanoclusters

Abstract: Thiolate‐protected gold nanoclusters (NCs) are promising catalytic materials for the electrochemical CO2 reduction reaction (CO2RR). In this work an atomic level modification of a Au23 NC is made by substituting two surface Au atoms with two Cd atoms, and it enhances the CO2RR selectivity to 90–95 % at the applied potential between −0.5 to −0.9 V, which is doubled compared to that of the undoped Au23. Additionally, the Cd‐doped Au19Cd2 exhibits the highest CO2RR activity (2200 mA mg−1 at −1.0 V vs. RHE) among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 56 publications
6
115
0
Order By: Relevance
“…Figure 1 c presents the simulated absorbance spectrum of [Ag 15 (C≡C−CH 3 ) 12 ] + along with the experimental one. To simplify the calculation, all C≡C‐ t Bu ligands are replaced with C≡C−CH 3 , which has been regarded as a common choice in the simulation of organic ligand‐protected clusters [32–37] . Note that this simplified treatment of the side groups has been demonstrated to show negligible effect on the electronic, optical, and catalytic behaviors when compared to the experimental bulky ligands, since the main optical transition and the catalytic active sites mainly derive from the metals, while the contributions from the side groups of the ligands are less significant.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 c presents the simulated absorbance spectrum of [Ag 15 (C≡C−CH 3 ) 12 ] + along with the experimental one. To simplify the calculation, all C≡C‐ t Bu ligands are replaced with C≡C−CH 3 , which has been regarded as a common choice in the simulation of organic ligand‐protected clusters [32–37] . Note that this simplified treatment of the side groups has been demonstrated to show negligible effect on the electronic, optical, and catalytic behaviors when compared to the experimental bulky ligands, since the main optical transition and the catalytic active sites mainly derive from the metals, while the contributions from the side groups of the ligands are less significant.…”
Section: Resultsmentioning
confidence: 99%
“…107 It has been reported that Au-based materials show high selectivity towards CO formation because the *CO intermediates on gold are relatively weak. 108 31 increased to 96% at -0.57 V for the electrocatalytic reduction of CO 2 to CO (Figure 12a and 12b), and the results exhibited that the partial current density of CO for Au 47 Cd 2 (TBBT) 31 is more negative than the Au 44 (TBBT) 28 nanocluster and the Au NPs (Figure 12c, Figure 12d) showed that electrocatalytic durability of Au 47 Cd 2 (TBBT) 31 is superiour to other materials. Most importantly, the results confirm that the CO 2 RR ability of Au 47 Cd 2 (TBBT) 31 is superior.…”
Section: Co 2 Rrmentioning
confidence: 95%
“…54. Copyright (2019) Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.driven CO 2 conversion over Au nanoclusters (Figure23) 55.…”
mentioning
confidence: 99%